Assessment of Selected Bioretention Blends for Nutrient Retention Using Mesocosm Experiments. Issue 5 (1st September 2014) - Liu, Jia; Sample, David J.; Owen, James S.; Li, Jinling; Evanylo, Gregory
Abstract : This study compares the performance of three bioretention media blends for N and P removal from simulated urban runoff in experimental mesocosms. TerraSolve, Biofilter, and "VT Mix" (Virginia Tech) were compared with and without vegetation at varying hydraulic residence times (HRTs). Adsorption isotherm experiments were also conducted. TerraSolve and VT Mix included water treatment residuals (WTRs), Biofilter and VT Mix included yard‐waste compost (YWC), and TerraSolve included a mix of coir and peat. TerraSolve removed the highest amount of total P (>95%), which is attributed to the high quantity of WTRs. Results were similar for VT Mix, likely due to WTR content. Adsorption isotherms indicate a substantial difference due to this factor. Vegetative mesocosms were found to be less effective at P removal at an HRT of 6 to 12 h but not at an HRT of 24 h. VT Mix had the highest removal of total Kjeldahl nitrogen (TKN), significantly different than the other blends. Interactive effects with vegetation were observed, generally improving TKN removal at all HRTs, with the highest at 24 h. Substantial export of nutrients when using compost was not observed. The addition of YWC appeared to increase N removal, possibly by denitrification. It is recommended that bioretention media contain <10% fines, a source of amorphous Al for P adsorption, at least 3 to 5% total organic C in the form of a low P, relatively stable compost, and a minimum concentration of plant‐available nutrients for establishment of vegetation. For systems that use HRT, optimum residence time is influenced by media composition.